The ANALYSIS OF KLABAT UNIVERSITY QUALITY OF SERVICE ON STUDENT SATISFACTION IN PAYING SPP BILLS: Kualitas Pelayanan, Kepuasan Mahasiswa, Populasi dan Sampel, Prosedur Pengumpulan Data, Analisis Koefisien Determinasi, Uji Parsial T - Jeiner Maruru; Tonny Irianto Soewignyo; Septiani Septiani (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2022)
This research was conducted with the aim of knowing the service quality of Klabat University, especially services from the finance department on student satisfaction in paying tuition fees. Sampling in this study used a stratified sampling method of 355 samples who were active students enrolled at Klabat University for the 2022/2023 academic year. By using multiple linear regression analysis, this study found that; the dimensions of responsiveness, empathy, and tangibility have a significant effect on student satisfaction, but the dimensions of reliability and assurance have no significant effect. The process of paying tuition fees and student financial reports still needs to be improved because there are still inaccurate numbers.